2004
DOI: 10.1111/j.1365-2702.2004.01008.x
|View full text |Cite
|
Sign up to set email alerts
|

Reflective practice and daily ward reality: a covert power game

Abstract: The realization of this covert power game by individual clinical nurses can become the incipient point for formally using reflective methods in the practice setting.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
81
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(83 citation statements)
references
References 42 publications
1
81
1
Order By: Relevance
“…The items reported as more satisfied were their feeling of well preparation for the required The study' results are supported with [37] and [38] who reported students satisfaction with placement mainly because they met their placement objectives, enjoyed their time and worked as a team who are willing and available staff that assisted them in learning. Studies conducted by [39] and [17] indicated that all students, regardless of location, rated higher satisfaction with their clinical experiences.…”
Section: Discussionsupporting
confidence: 70%
“…The items reported as more satisfied were their feeling of well preparation for the required The study' results are supported with [37] and [38] who reported students satisfaction with placement mainly because they met their placement objectives, enjoyed their time and worked as a team who are willing and available staff that assisted them in learning. Studies conducted by [39] and [17] indicated that all students, regardless of location, rated higher satisfaction with their clinical experiences.…”
Section: Discussionsupporting
confidence: 70%
“…Dilworth et al, 2013, Mantzoukas, 2004, which, based on our interpretation, suggests that similar differences might exist there between the nursing and clinical supervision cultures. In short, some important aspects of the nursing environment culture, which contrast with the culture of supervision identified in the Czech context, have also been found by researchers in other countries.…”
Section: Discussionmentioning
confidence: 99%
“…Given the research evidence regarding the similarities between some aspects of nursing culture in various countries (e.g. Dilworth et al, 2013, Mantzoukas, 2004), the paradigm model titled "Clinical Supervision: Challenging the Nursing Environment?" might be a source of inspiration beyond the Czech context from within which it arose.…”
Section: Review Of European Studiesmentioning
confidence: 99%
“…A dysfunctional environment can lead to an arena for a covert power game [42] where nurses can become powerful gatekeepers to the community of practice by jointly deciding if they aim to support each other by sharing knowledge or not. This is a subtle selection, shown in the workplace culture, of who is allowed to influence the meaning and learning in the community of practice.…”
Section: "If I Would Like To Have Something Else Then I Do Not Get Amentioning
confidence: 99%